Early Recurrence in Resected Gallbladder Carcinoma: Clinical Impact and Its Preoperative Predictive Score - Yuji, Shimizu; Ryo, Ashida; Teiichi, Sugiura; Yukiyasu, Okamura; Katsuhisa, Ohgi; Mihoko, Yamada; Shimpei, Otsuka; Takeshi, Aramaki; Akifumi, Notsu; Katsuhiko, Uesaka (Annals of Surgical Oncology, 2022)
Background Surgical resection is the only potentially curative therapy for gallbladder carcinoma (GBC). However, the postoperative recurrence rate is high (approximately 50%), and recurrence occasionally develops early after surgery. Patients and Methods A total of 139 patients who underwent macroscopically curative resection for GBC between 2002 and 2018 were retrospectively reviewed. Early recurrence (ER) was defined as recurrence within 6 months after surgery. Univariate and multivariate logistic regression analysis was performed using preoperative factors that may influence early recurrence, namely patient background factors, tumor markers, imaging findings, and body composition parameters obtained preoperatively, to create a predictive score for ER. Results The median follow-up period was 21.9 months (range, 6.2–195.7 months). Postoperative recurrence was observed in 55 (39.6%) patients, of whom 14 (25.5%) developed ER. The median overall survival after surgery was 104.7 months for the non-ER group and 15.7 months for the ER group. On multivariate analysis, high carbohydrate antigen 19-9, low muscle attenuation, high visceral fat attenuation, liver invasion, and other organ invasion on preoperative computed tomography were identified as independent risk factors for ER. A preoperatively predictive scoring system for ER was constructed by weighting the above five factors. The nomogram showed an area under the curve of 0.881, indicating good predictive potential for ER. Conclusions ER in resected GBC indicates a very poor prognosis. The present preoperative scoring system can sufficiently predict ER and may be helpful in determining the optimal treatment strategies.